Rozwój gospodarczy Irlandii na podstawie niektórych wskaźników makroekonomicznych - Kowalik, Paweł (Economic Development of Ireland Based on Some Macroeconomic Rates, 2007)
Ireland has belonged to the European Union for over 30 years. The country has transformed from the poorest member state of the European Union to a rich one. Gross Domestic Product (GDP) per capita is nowadays above the average of the GDP of the European Union member states. The article is a attempt to present the changes of some macroeconomic rates which have influenced that situation. Its author also tries to analyse if structural help of the European Union has had an influence on economic development of Ireland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 200-212